SISTEM PEMBUKTIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (KDRT) PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (Studi Di Unit Perlindungan Perempuan Dan Anak Polisi Resor Musi Rawas) - Samsul Samsul (Qiyas : Jurnal Hukum Islam dan Peradilan, 2018)
The results of this study are 1) Proof of crime, domestic  violence in the perspective of Islamic law using 4 evidences namely  iqrar  (existence  of recognition), Bayyinah  (testimony),  Qasamah (oath),  and  Qarinah (signs or guidance), 2) proof (Article 184 of the Indonesian Criminal Code)  using 6 Legal evidence  of witness testimony,  expert  statement, letter, guidance, and description  of the defendant 3) similarity of proof of crime Domestic Violence between  Islamic law And the positive law of the two laws equally uses testimony of witnesses or testimonies,  evidence  of guidance, testimony of the accused  or acknowledg- ment,  and  oath,  4) the difference  in the way of proofing  the crime of domestic  violence  between  Islamic law and  positive law lies in the witness (testimony)  , And proof of crime in Islamic law does  not use proof of letter, expert  witness or expert  witness testimony,  4) criminal acts Domestic Violence (KDRT) in the jurisdiction Police Resort Musi Rawas caused  by economic factors, drug problems, frequent  drinking, gambling,  and infidelity